2011
DOI: 10.1016/j.jcis.2011.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive removal of arsenic from water by an iron–zirconium binary oxide adsorbent

Abstract: a b s t r a c tArsenate and arsenite may exist simultaneously in groundwater and have led to a greater risk to human health. In this study, an iron-zirconium (Fe-Zr) binary oxide adsorbent for both arsenate and arsenite removal was prepared by a coprecipitation method. The adsorbent was amorphous with a specific surface area of 339 m 2 /g. It was effective for both As(V) and As(III) removal; the maximum adsorption capacities were 46.1 and 120.0 mg/g at pH 7.0, respectively, much higher than for many reported a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
103
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 257 publications
(117 citation statements)
references
References 40 publications
13
103
1
Order By: Relevance
“…2a. It demonstrates two broad peaks at approximately 35.1 and 62.2 , respectively, which are similar to those of poorly ordered 2-line ferrihydrite (Schwertmann and Cornell, 2000;Ren et al, 2011). This indicates that the prepared FeeCu binary oxide is amorphous and 2-line ferrihydrite-like.…”
Section: Characterization Of 1:2 Feecu Binary Oxidementioning
confidence: 73%
See 1 more Smart Citation
“…2a. It demonstrates two broad peaks at approximately 35.1 and 62.2 , respectively, which are similar to those of poorly ordered 2-line ferrihydrite (Schwertmann and Cornell, 2000;Ren et al, 2011). This indicates that the prepared FeeCu binary oxide is amorphous and 2-line ferrihydrite-like.…”
Section: Characterization Of 1:2 Feecu Binary Oxidementioning
confidence: 73%
“…Li et al (2010) synthesized a CeeTi oxide sorbent with high efficiency at both As(V) and As(III) removal. Ren et al (2011) found that an FeeZr binary oxide prepared in their laboratory had high sorption capacity towards arsenic.…”
Section: Introductionmentioning
confidence: 99%
“…The Fe-Zr binary oxide was prepared according to the following procedure, which has been described in our previous publication (Ren et al 2011): Ferric chloride hexahydrate (FeCl 3 ·6H 2 O, 0.05 mol) and zirconyl chloride octahydrate (ZrOCl 2 ·8H 2 O, 0.0125 mol) were dissolved in 400 ml deionized water. Under vigorous magnetic-stirring, sodium hydroxide solution (2 M) was added dropwise to raise the solution pH to around 7.5.…”
Section: Preparation Of Fe-zr Binary Oxidementioning
confidence: 99%
“…Thus, it is expected that an iron-zirconium composite material originated from the combination of iron oxide and zirconium oxide may take full use of the advantages of both parent materials and have the potential for phosphate removal. In our previous studies (Ren et al 2011), an iron-zirconium (Fe-Zr) binary oxide was synthesized and was found to have high adsorption capacities towards both arsenate and arsenite. Furthermore, phosphate was found to be the most competitive anion for arsenic adsorption by the binary oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-component sorbents often exhibit different sorption behaviors compared to single-component sorbents [20,21]. It is believed that the differences in physical-chemical properties between multi-and single-component solids are the primary reason for the differences in sorption behaviors.…”
Section: Introductionmentioning
confidence: 99%